Social Capital as Investment in the Future: Kinship Relations in Financing Children's Education during Reforms in a Vietnamese Village - Nguyen, Anh Tuan; Thomése, Fleur; Salemink, Oscar (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
This paper identifies how social capital in kinship relations is employed to foster children’s education in the Reform era (Đổi mới), based on an anthropological and sociological study in Quỳnh Đôi village, Quỳnh Lưu district, Nghệ An province, Vietnam. The paper shows that in the Đổi mới period, with the state policy of ‘socialization of education’, many social forces have contributed to educational affairs. In rural areas in northern Vietnam, kinship institutions such as patrilineage groups have played an important role in supporting children’s education through “study encouragement funds” [quỹ khuyến học]. From a social capital perspective, we argue that social capital, understood as enforceable trust and reciprocity exchanges, was the foundation for raising patrilineage study encouragement funds. One significant observation was that both patrilineage members and non-members contributed to these funds. Moreover, pupils receiving financial study encouragements could be either patrilineage members or non-members. Thus, the kin-based support system for children’s education has gone beyond the boundaries of patrilineage kin groups to include both patrilineal and other kin relations. From a receiver’s viewpoint, the social capital benefiting pupils was located in ego-based kinship networks which extended beyond just patrilineages. Therefore, in the Đổi mới era, villagers went beyond their patrilineage boundaries to mobilize social capital in their ego-based kin networks, including both relatives inside and outside their patrilineage, to encourage children’s education.